A Study on the Fatty Acid Profile and Conjugated Linoleic Acid (CLA) Content in Common Thai Indigenous Chickens Raised by Natural Farming in Nakhon Phanom Province - Tanom TATHONG; Santisook WORRAWATTANATAM (Walailak Journal of Science and Technology, 2011)
This research studied the fatty acid profile and conjugated linoleic acid (CLA) content in common Thai indigenous chickens (5 months old) raised by natural farming in Nakhon Phanom province. One hundred and ten chickens (55 females and 55 males) with an average weight of 955 g and 1,050 g for females and males respectively were selected for the experiment. The chickens were randomly selected and meat samples were collected to determine the fatty acid profile and CLA content. The results showed that the saturated fatty acids (SFA) in males were composed mainly of C16:0, C14:0 and C15:0 while in females they were composed of C22:0, C15:0 and C16:0. The most common monounsaturated fatty acids (MUFA) in males and females were C24:1 and C15:1 respectively. The most common polyunsaturated fatty acid (PUFA) for both males and females was C20:3n3. The highest CLA profile was found in chicken meat cis9trans11 in males and females. The total fatty acid profile in breast meat showed that males had higher amounts of MUFA than females (p < 0.05) but that females had higher amounts of SFA and CLA than males (p < 0.05) while the amount of PUFA was similar in both males and females (p > 0.05).